2009
DOI: 10.1051/0004-6361/200811085
|View full text |Cite
|
Sign up to set email alerts
|

MOND and the dark baryons

Abstract: We consider for the first time the implications for the modified gravity MOND model of galaxies, of the presence of dark baryons, in the form of cold molecular gas in galaxy discs. We show that MOND models of rotation curves are still valid and universal, but the critical acceleration a 0 separating the Newtonian and MONDian regimes has a lower value. We quantify this modification as a function of the scale factor c between the total gas of the galaxy and the measured atomic gas. The main analysis concerns 43 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…This Figure shows that about half of galaxies in the sample (72 out of 153 galaxies or 47%) could contain some dark baryons because the c-values for these galaxies is in the range of 1 < c < 10, and (53%) of galaxies have a scale factor of 1, equivalent to a model without dark baryons. The mean values of the scale-factor are < c >= 2.1 ± 1.7 and 2.7 ± 1.7 for Models A.2 and A.3, respectively, in agreement with the previous works such as Tiret & Combes (2009).…”
Section: Standard Interpolating Functionsupporting
confidence: 91%
See 1 more Smart Citation
“…This Figure shows that about half of galaxies in the sample (72 out of 153 galaxies or 47%) could contain some dark baryons because the c-values for these galaxies is in the range of 1 < c < 10, and (53%) of galaxies have a scale factor of 1, equivalent to a model without dark baryons. The mean values of the scale-factor are < c >= 2.1 ± 1.7 and 2.7 ± 1.7 for Models A.2 and A.3, respectively, in agreement with the previous works such as Tiret & Combes (2009).…”
Section: Standard Interpolating Functionsupporting
confidence: 91%
“…On the other hand, the empirically strong correlation between the baryonic, Newtonian acceleration and the dynamical acceleration V 2 (R)/R at the same position (RAR), is one of the major predictions of modified Newtonian dynamics (MOND) (Milgrom 1983a(Milgrom , 2016bCombes & Tiret 2010). Indeed the presence of dark molecular gas increases the baryonic mass and hence reduces the critical acceleration of MOND, the result that was later confirmed by Tiret & Combes (2009) who found that the observed rotational velocities of a sample of 43 spiral galaxies can be explained in the framework of MOND with a lower value of a 0 1 and the best-fitting c-value of 3.…”
Section: Some Cosmological Evidences Such As Cosmic Microwavementioning
confidence: 91%
“…Legend as in Fig. 1. assumption of cold unobservable molecular gas in the galactic disk (Tiret & Combes 2009) leads to better fits with lower χ 2 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Interpretation of the BTF relation in the context of MOND leads to the estimate a0 = cm/s 2 [10]. The transition between these limiting cases can be described by a simple expression [30]:…”
Section: Rotation Curve Plotting In the Mond Modelmentioning
confidence: 99%